2012
DOI: 10.1021/jp3065322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Water Content on the Diffusion Coefficients of Li+ and Water across Naphthalenic Based Copolyimide Cation-Exchange Membranes

Abstract: The transport of lithium ions in cation-exchange membranes based on sulfonated copolyimide membranes is reported. Diffusion coefficients of lithium are estimated as a function of the water content in membranes by using pulsed field gradient (PFG) NMR and electrical conductivity techniques. It is found that the lithium transport slightly decreases with the diminution of water for membranes with water content lying in the range 14 < λ < 26.5, where λ is the number of molecules of water per fixed sulfonate group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…PFG NMR has been widely used to characterize the water diffusion coefficient in polymer membrane systems ,,, and it is used here in a similar fashion. The dependence of D H 2 O on the water content for five types of PFSA membranes is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…PFG NMR has been widely used to characterize the water diffusion coefficient in polymer membrane systems ,,, and it is used here in a similar fashion. The dependence of D H 2 O on the water content for five types of PFSA membranes is shown in Figure b.…”
Section: Resultsmentioning
confidence: 99%
“…23,24,25,26 Fluorescence techniques combined with MD simulations have been used successfully for studying the effect of hydration 27,28 and solvent penetration 29,30 on membrane properties. 31,32,33 …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Figure illustrates the variation of the molar conductivity of lithium with the concentration of various electrolytes in water, specifically lithium acetate, lithium triflate, and lithium chloride (data from ref ), and the corresponding values found in the lithium hydrogel networks. It is observed that there is a great reduction of the molar conductivity of lithium in the networks compared to that in solution.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 8. Variation of the molar conductivity of lithium with the concentration of various electrolytes in water, specifically lithium acetate (black squares), lithium triflate (green triangles), and lithium chloride35 (red circles), and the corresponding values found in the lithium hydrogel networks (blue triangles).…”
mentioning
confidence: 99%